0
$\begingroup$

I need help with this question:

Let $f: X \to Y$ be a function, and let $A$ be a subset of $X$. Why are the sets $A$ and $f^{-1}(f(A))$ not necessarily equal? Under what conditions are they equal?

Thanks!

$\endgroup$
1
$\begingroup$

Consider the function $f:\{1,2,3\}\rightarrow\{2,3,4\}, f(1)=2, f(2)=f(3)=3$ and let $A=\{1,2\}\subseteq\{1,2,3\}$.

$f(A)=f(\{1,2\})=\{2,3\}\implies f^{-1}(f(A))=f^{-1}(\{2,3\})=\{1,2,3\}\neq\{1,2\}=A$


We define the direct image of $A\subseteq X$ as $f(A)=\{f(x): x\in A\}$ and the inverse image of $B\subseteq Y$ as $f^{-1}(B)=\{x: x\in X, f(x)\in B \}$. Clearly, the inverse image of $f(A)$, that is $f^{-1}(f(A)),$ contains all the elements of $A$ as $f(x)\in f(A),\ \forall x\in A$. This means $A\subseteq f^{-1}(f(A))$. But this is not to say that $f^{-1}(f(A))$ contains only the elements of $A$. If $\exists\ y\in X-A$ such that $f(y)\in f(A)$, then $y\in f^{-1}(f(A))$ but $y\notin A$.

The sufficient and necessary condition for $f^{-1}(f(A))=A,\ \forall A\subseteq X$, is that $f$ is injective. You already know from above that $A\subseteq f^{-1}(f(A))$. Can you prove the converse: $f^{-1}(f(A))\subseteq A,\forall A\subseteq X$ given $f$ is injective?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.